Cardiorespiratory Kinetics Determined by Pseudo-Random Binary Sequences – Comparisons between Walking and Cycling - Koschate, J.; Drescher, U.; Thieschäfer, L.; Heine, O.; Baum, K.; Hoffmann, U. (International Journal of Sports Medicine, 2016)
This study aims to compare cardiorespiratory kinetics as a response to a standardised work rate protocol with pseudo-random binary sequences between cycling and walking in young healthy subjects. Muscular and pulmonary oxygen uptake (V̇O2) kinetics as well as heart rate kinetics were expected to be similar for walking and cycling. Cardiac data and V̇O2 of 23 healthy young subjects were measured in response to pseudo-random binary sequences. Kinetics were assessed applying time series analysis. Higher maxima of cross-correlation functions between work rate and the respective parameter indicate faster kinetics responses. Muscular V̇O2 kinetics were estimated from heart rate and pulmonary V̇O2 using a circulatory model. Muscular (walking vs. cycling [mean±SD in arbitrary units]: 0.40±0.08 vs. 0.41±0.08) and pulmonary V̇O2 kinetics (0.35±0.06 vs. 0.35±0.06) were not different, although the time courses of the cross-correlation functions of pulmonary V̇O2 showed unexpected biphasic responses. Heart rate kinetics (0.50±0.14 vs. 0.40±0.14; P=0.017) was faster for walking. Regarding the biphasic cross-correlation functions of pulmonary V̇O2 during walking, the assessment of muscular V̇O2 kinetics via pseudo-random binary sequences requires a circulatory model to account for cardio-dynamic distortions. Faster heart rate kinetics for walking should be considered by comparing results from cycle and treadmill ergometry.
Keywords: circulatory model; cycle ergometry; treadmill ergometry; heart rate kinetics; oxygen uptake kinetics